In Vitro Studies on Phytochemical Evaluation and Antimicrobial Properties of Pleurotus florida - Thota, Prabhakar; Bhogavalli, Praveen kumar; Gangula, Shirish reddy.; Peddapuram, Lakshmi Narayana (Asian Journal of Biological and Life Sciences, 2012)
The present study scientifically examined the phytochemistry and antimicrobial potencies of two organic extracts of Pleurotus florida. Generally, both extracts were effective against 89.8% of the isolates tested with Bacillus subtilis (10-10.2mm) and Escherichia coli (8.6-9 mm) exhibiting highest gram +ve and gram -ve by agar well diffusion method, respectively. However, petroleum ether extract (PE) exhibited greater anti-gram -ve bacterial activity than the acetone extract (AE) and further produced growth inhibition of these isolates in broth. The phytochemical analyses of the extracts revealed the presence of terpenoids, tannins, steroidal glycosides, carbohydrates and Flavonoids. While the presence of alkaloids, carboxylic acids, Volatile oils, Cardinolides, Resins, Quinones, fatty acids and cynogenic glycosides were not detected. The results indicate that P. florida possesses antimicrobial activity.